2007
DOI: 10.1152/ajpheart.00401.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy signaling during peripartum cardiac remodeling

Abstract: Pregnancy is associated with physiological cardiac hypertrophy. There is rapid reversal of hypertrophy in the PP period while recovery of cardiac function is delayed, possibly related to PP upregulation of JNK. A dysregulation of MAPK signaling may be an important determinant of PP cardiac dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
8
28
0
Order By: Relevance
“…However, none of the parameters measured supported the evidence of significant cardiac hypertrophy in pregnant Wistar rats. These findings are in contrast to some other studies performed in rats [2], [18][20], but in line with our previous study in Wistar rats [8]. Our present study had 80% statistical power to detect an increase in HW of 13% due to pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…However, none of the parameters measured supported the evidence of significant cardiac hypertrophy in pregnant Wistar rats. These findings are in contrast to some other studies performed in rats [2], [18][20], but in line with our previous study in Wistar rats [8]. Our present study had 80% statistical power to detect an increase in HW of 13% due to pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…In late-pregnant mice, an increase in heart weight but a decrease in the heart-to-body weight ratio was observed [18]. In 16-daypregnant rats, there was no significant change in heart-tobody weight when compared to nonpregnant rats (estrus cycle stage unknown) [24], while in this study we found that in late-pregnant rats (18-21 days) the heart-to-body weight ratio increased when compared to nonpregnant (diestrus) and postpartum animals.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have shown there is a unique system of molecular signaling pathway involved in pregnancy-induced hypertrophy [2224]. The ubiquitin-proteasome system is known to play an important role in the degradation of damaged and misfolded proteins in the heart [25].…”
Section: Discussionmentioning
confidence: 99%